1998
DOI: 10.1051/lait:1998223
|View full text |Cite
|
Sign up to set email alerts
|

Rapid identification of dairy Propionibacterium species by restriction analysis of the insertion within the 23S rRNA gene

Abstract: -An amplified sequence of approximately 350 bases from the 23S rRNA gene of each bacteria was used to identify 37 strains of dairy propionibacteria. After generation of the fragment by PCR (polymerase chain reaction), it was eut with the restriction endonuclease MspI. The resulting electrophoretic pattern showed a distinct profile for each of the Propionibacterium species. Purification of DNA was not necessary and the analyses could also be performed with crude bacterial extract. A collection of anaerobie bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Identification of Propionibacterium species was performed according to Fessler, Casey, and Puhan (1998). Briefly, part of the 23S rDNA was amplified followed by restriction analysis with MspI (New England Biolabs, Ipswich, MA, USA).…”
Section: Identification and Genotyping Of Propionibacteriamentioning
confidence: 99%
“…Identification of Propionibacterium species was performed according to Fessler, Casey, and Puhan (1998). Briefly, part of the 23S rDNA was amplified followed by restriction analysis with MspI (New England Biolabs, Ipswich, MA, USA).…”
Section: Identification and Genotyping Of Propionibacteriamentioning
confidence: 99%
“…Although the culture-independent assay was shown to yield similar results when compared with plate count assays, the study concluded that plate counts were more accurate than qPCR for cell concentrations below 10 3 cells/g of food. In the present study, sodium lactate agar was used for the initial growth step since this medium was previously shown to enable growth of all species of dairy propionibacteria (Fessler et al 1998). …”
Section: Stability Of Is-rflp and Mlva Patternsmentioning
confidence: 99%
“…In practice, the introduction of these systems resulted in a drastic reduction of cases of late fermentation during the long-term ripening of Emmentaler PDO cheese. Propionibacteria are naturally present in raw milk at concentrations of 10 1 -10 3 cfu.mL -1 , and little is known regarding their influence on Emmentaler PDO cheese quality (Fessler et al 1997;Fessler et al 1998).…”
Section: Introductionmentioning
confidence: 99%